2021
DOI: 10.5812/zjrms.92588
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effect of Laparoscopic Cholecystectomy on Coagulation Tests Among Patients Undergoing the Surgery in Ali Ibn Abi Taleb Hospital in Zahedan in 2018

Abstract: Background: Laparoscopic cholecystectomy, one of the most common elective surgical procedures, is a minimally invasive surgical procedure for patients with gallbladder diseases. Objectives: This study aimed to evaluate the effect of laparoscopic cholecystectomy on coagulation tests among patients undergoing the surgery in Ali Ibn Abi Taleb Hospital in Zahedan. Methods: Following a quasi-experimental design, 21 cases scheduled for laparoscopic cholecystectomy for whatever reasons at Ali Ibn Abi Taleb Hospital i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Two independent studies published by Shahraki et al and Garg et al revealed a significant change only in PT after laparoscopic cholecystectomy, with no significant effects on other coagulation factors. This difference was attributed to the severe catabolic response of the liver postoperatively [61,62]. Regarding the effect of intraoperative biliary mapping on the coagulation mechanism, the literature evidence is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Two independent studies published by Shahraki et al and Garg et al revealed a significant change only in PT after laparoscopic cholecystectomy, with no significant effects on other coagulation factors. This difference was attributed to the severe catabolic response of the liver postoperatively [61,62]. Regarding the effect of intraoperative biliary mapping on the coagulation mechanism, the literature evidence is scarce.…”
Section: Discussionmentioning
confidence: 99%